The E-A-S-I (Exposure-Analogy Visual-Social Action-Impact Writing) Learning Model: Improving Reflective Writing Skills and Developing Values in Elementary School through Wayang Sukuraga - Lyesmaya, Dyah; Musthafa, Bachrudin; Sunendar, Dadang; Rahman; fahrurrozzi, Fahrurrozzi (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2023)
This research aims to develop a literacy learning model based on the visual analogy of Wayang Sukuraga as a construction of values in reflective writing for elementary school students. EASI integrates the visual analogy media of Wayang Sukuraga with reflective writing learning to enhance understanding and value development in writing. The inadequate literacy programs in elementary schools, especially in students' writing abilities integrated with local wisdom values, became the background of this research. As a solution, the author developed a literacy learning model based on the visual analogy of Wayang Sukuraga and conducted a limited test and effectiveness of this model in seven elementary schools in Sukabumi City. This research used a research and development method involving the stages of development, validation, and implementation of the learning model. The research subjects were elementary school students in seven schools in Sukabumi City, in the area where Wayang Sukuraga originated. Data were collected through observation, interviews, questionnaires, and written tests. The results of the research showed that this model is effective in improving reflective writing skills and constructing values in students, especially in religious values, honesty, courage, independence, cooperation, and hard work. The visual analogy of Wayang Sukuraga proved to be an effective means of facilitating literacy learning for students, so the development of a literacy learning model based on the visual analogy of Wayang Sukuraga can be an effective alternative for improving reflective writing skills and value construction in elementary school students in Sukabumi City. Furthermore, this model is also effective in facilitating a more active, creative, and enjoyable learning process for students.